Machine learning-based approaches for tomato pest classification - Gayatri Pattnaik; Kodimala Parvathy (Universitas Ahmad Dahlan, 2022)
Insect pests are posing a significant threat to agricultural production. They live in different places like fruits, vegetables, flowers, and grains. It impacts plant growth and causes damage to crop yields. We presented an automatic detection and classification of tomato pests using image processing with machine learning-based approaches. In our work, we considered texture features of pest images extracted by feature extraction algorithms like gray level co-occurrence matrix (GLCM), local binary pattern (LBP), histogram of oriented gradient (HOG), and speeded up robust features (SURF). The three standard classification methods, including support vector machine (SVM), k-nearest neighbour (k-NN), and decision tree (DT) are used for classification operation. The three classifiers have undergone a comprehensive analysis to present which classifier with which feature yields the best accuracy. The experiment results showed that the SVM classifier's precision using the feature extracted by local binary patterns (LBP) algorithm achieves the highest value of 81.02%. MATLAB software used for feature extraction and waikato environment for knowledge analysis (WEKA) graphical user interface for classification.